Online Behavior Modification Therapy: A Case Study on Enhancing Task Initiation in a Child with ADHD - Rahmania, Farra Anisa (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Children with attention-deficit/hyperactivity disorder (ADHD) often experience difficulties in maintaining attention on tasks, display impulsive behaviors, and show signs of hyperactivity. Therefore, interventions are needed to help children manage ADHD symptoms. This study specifically aimed to examine the effectiveness of online behavior modification therapy using the response cost technique in enhancing task initiation in a child with ADHD. The study employed a single-case design. The participant was a 10-year-old child (n=1) who exhibited ADHD symptoms, including difficulties sustaining attention, impulsivity, and hyperactivity. Assessments were conducted through observation, interviews, and psychological testing. ADHD symptoms were measured using the Indonesian Attention-Deficit Hyperactivity Disorder Rating Scale (IARS). The intervention lasted for 5 weeks. Baseline psychological conditions were assessed to guide the intervention plan. Following the intervention, several improvements were observed, including a reduction in IARS scores (from 69 to 61), increased initiative in task completions, greater attentiveness during conversations, and a decrease in impulsive behaviors. However, as this study used a single-case design, the findings cannot be generalized, and further research is needed to better understand the effectiveness of this intervention for other children with ADHD. This study may serve as a reference for mental health professionals in managing ADHD cases in children.